2016
DOI: 10.1002/lio2.26
|View full text |Cite
|
Sign up to set email alerts
|

Taste Receptors: Regulators of Sinonasal Innate Immunity

Abstract: Taste receptors in the oral cavity guide our preferences for foods, preventing toxic ingestions and encouraging proper nutrient consumption. More recently, expression of taste receptors has been demonstrated in other locations throughout the body, including the airway, gastrointestinal tract, pancreas, and brain. The extent and specific roles of extraoral taste receptors are largely unknown, but a growing body of evidence suggests that taste receptors in the airway serve a critical role in sensing bacteria and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 108 publications
(327 reference statements)
1
40
0
Order By: Relevance
“…Previous studies demonstrated that individuals with a nonfunctional T2R38 allele having significantly blunted NO and ciliary responses following exposure to gram‐negative quorum‐sensing molecules are infected with gram‐negative bacteria, such as Pseudomonas aeruginosa , and develop CRS. Therefore these individuals are more likely to need surgery than those with functional receptor alleles …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies demonstrated that individuals with a nonfunctional T2R38 allele having significantly blunted NO and ciliary responses following exposure to gram‐negative quorum‐sensing molecules are infected with gram‐negative bacteria, such as Pseudomonas aeruginosa , and develop CRS. Therefore these individuals are more likely to need surgery than those with functional receptor alleles …”
Section: Discussionmentioning
confidence: 99%
“…Therefore these individuals are more likely to need surgery than those with functional receptor alleles. 8,13 Based on this hypothesis, we compared the microbiology of sinonasal mucosa of PAV/PAV patients to those with other genotypes. Our findings confirmed data in the literature in which gram-negative infections are mainly associated with the AVI haplotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic rhinosinusitis (CRS) is an inflammatory disease of the paranasal sinus mucosa that causes a significant detriment to quality of life, results in billions of dollars in related costs, and has a largely unknown pathophysiology, although multiple possible mechanisms have been proposed . The natural history of CRS includes chronic nasal and extranasal symptoms as well as acute and transient increases in symptoms referred to as acute exacerbations of CRS (AECRS) .…”
Section: Introductionmentioning
confidence: 99%